ANALISIS PENGARUH AL-QUR’AN DIGITAL TERHADAP MINAT BACA MAHASISWA DI TENGAH TINGGINYA KESIBUKAN AKADEMIK - Zaskia Cahya Ramadhani; Zaskia Talita Putri; Awaahin Qalbi Aany; Roni Hidayat (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to examine the impact of digital Quran utilization on students’ reading interest amidst demanding academic schedules using a descriptive quantitative approach. Data collected through online questionnaires distributed to highly mobile students indicate that the accessibility of the digital Quran (Variable X) exerts a significant positive effect, with 60% of respondents finding the technology’s convenience highly beneficial. Regarding Variable Y (Reading Interest), the findings reveal that 55% of students maintain productivity by reading more than 10 verses per session through micro-reading strategies despite their busy schedules. Although challenges such as time constraints (50%) and physical exhaustion (25%) persist, digital technology proves to be an effective tool for bolstering spiritual resilience. Ultimately, this research concludes that the digital Quran not only facilitates easier access but also strengthens positive habits and religious literacy among the younger generation.